(untitled) (International relations and international law Journal, 2019)
Regional integration, or convergence and cooperation, is one of the main topic of international discourse. Meanwhile, the progress of scientific research in Central Asia in this respect is not sufficient. It is mostly represented by popular science literature, quite syperficial in describing the latest integraton activities either in Central Asia or the EAEU. In this article, an attempt into scientific understanding of the processes taking place in Central Asia and, more broadly, Eurasia; an attempt to comprehend how do they correlate with the real course of regional integration are represented. The analysis of the gradual development of the post-Soviet area leads to the results that have ambiguous definitions. The authors are asking themselves whether the integration phenomena that are still transforming and ot finalized yet can be defined as real integration. Along with this, it is appropriate to to draw parallels and determine correlation bonds between the mechanisms and the institutes of the functioning regional association of the integration type (the EAEU) with the Eurasian idea projects proposed by the the post-Soviet area countries. In the scientific literature, the high political ans state level, in the frameworks of which the key decisions on the need for integrations are being made, is being researched thoroughly. Such decisions are represented by the rational choice in the security dilemma issue, as well as social welfare and sustainable development of the Central Asian and Eurasian regions. In this article, we will try to analyse in a bundle the selected issues of the political idea (projects) regarding regional integration and its prospects. Key words: Central Asia, Eurasian idea, integration, cooperation, Eurasian Union.